2003
DOI: 10.1097/00007435-200303000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chlamydia trachomatis Infection in Registered Female Sex Workers in Northern Mexico

Abstract: C trachomatis is an important pathogen in the sexually transmitted diseases of registered FSWs in northern Mexico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…( 7 ) In addition, the prevalence of chlamydia in our study population was higher than other studies of female sex workers. ( 7 , 12 , 13 ) The 25% chlamydia incidence in the women in our study is nearly twice that shown in a study of pregnant women from the general population in Kiribati. ( 9 ) This substantial difference highlights the increased STI risk for sex workers and emphasizes the need for public health interventions.…”
Section: Discussionsupporting
confidence: 49%
“…( 7 ) In addition, the prevalence of chlamydia in our study population was higher than other studies of female sex workers. ( 7 , 12 , 13 ) The 25% chlamydia incidence in the women in our study is nearly twice that shown in a study of pregnant women from the general population in Kiribati. ( 9 ) This substantial difference highlights the increased STI risk for sex workers and emphasizes the need for public health interventions.…”
Section: Discussionsupporting
confidence: 49%
“…7 In addition, the prevalence of chlamydia in our study population was higher than other studies of female sex workers. 7,12, 13 The 25% chlamydia incidence in the women in our study is nearly twice that shown in a study of pregnant women from the general population in Kiribati. 9 This substantial difference highlights the increased STI risk for sex workers and emphasizes the need for public health interventions.…”
Section: Discussionsupporting
confidence: 43%
“…The frequency of C. trachomatis detected by PCR in this study was 14.5%. Previous studies in Mexican populations have detected C. trachomatis at frequencies ranging from 1.5% to 28% [ 10 , 11 ]. Our results thus fall within the reported range for Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented C. trachomatis frequencies ranging from 1.5 to 28% in female populations in Mexico [ 10 , 11 ]. The only Mexican study that has included reporting on C. trachomatis genotypes showed that 24 of 152 (15.8%) infertile patients were positive for C. trachomatis , and that the most prevalent genotype was F [ 12 ].…”
Section: Introductionmentioning
confidence: 99%